MoS2 nanosheets direct supported on reduced graphene oxide: An advanced electrocatalyst for hydrogen evolution reaction - Cao, Jiamu; Zhou, Jing; Zhang, Yufeng; Zou, Yuezhang; Liu, Xiaowei (PloS one, 2017)
Molybdenum disulfide nanosheets/reduced graphene oxide (MoS2 NSs/rGO) nanohybrid as a highly effective catalyst for hydrogen evolution reaction (HER) have been successfully synthesized by a facile microwave-assisted method. The results clearly reveal that direct grown of MoS2 NSs on rGO have been achieved. Electrochemical tests show that the as-prepared hybrid material exhibited excellent HER activity, with a small Tafel slope of 57 mV dec-1, an overpotential of 130 mV and remarkable cycling stability. After analysis, the observed outstanding catalytic performance can be attributed to the uniform distribution of the MoS2 NSs, which are characterized by the presence of multiple active sites as well as the effective electron transport route provided by the conductive rGO substrate. Moreover, according to the classic theory, the mechanism governing of the catalytic HER on the MoS2 NSs/rGO nanohybrid has been clarified.